Analisis Kualitas Air Sumur Gali Di Kelurahan Maubeli Kota Kefamenanu Kabupaten Timor Tengah Utara - Suni, Yunita; Fallo, Gergonius; Blegur, Willem Amu (Program Studi Biologi, Universitas Timor, 2024)
The existance of dug well is important for the people of Maubeli from Kefamenanu City. The society consumed it since their adults been there. As quality as water consuming needed to be tested for sanitation and hyegene issues. The aims is to analyze dug water quality in Maubeli Village for physic parameters (temperature, odor, colour, TSS), chemistry (pH, COD, and microbiology (E.coli). Water sample from 5 locations and analized locally for temperature, odor, colour, pH and in Laboratorium Dinas Lingkungan Hidup dan Kehutanan from East Nusa Tenggara for TSS dan COD. Data compared to Peraturan Pemerintah No. 22/2021 and Permenkes No. 2/2023. The resulst showed that the temperature for 1st dan 2nd are 250C, 3rd to 5th: 270C, there’s good for odor and colour. TSS: 2,5 mgL-1, 3,5 mgL-1, 9 mgL-1, 4 mgL-1, and 5 mgL-1. pH: (8,1), (7,9), (8,2), (7,9), and (7,6). COD: 15,16 mgL-1, 17,02 mgL-1, 9,61 mgL-1, 12,05 mgL-1, and not found E. coli for all dug wells. Base on snapshot sampling that the water quality is good to be consumed but still need to boil it.